Lesbian, gay, bisexual, trans, intersex, and queer psychology an introduction - Ellis, Sonja J.; Peel, Elizabeth; Riggs, Damien W. (Cambridge, United Kingdom Cambridge University Press, 2020)
"The second edition of this award-winning textbook provides an accessible and engaging introduction to the field of lesbian, gay, bisexual, transgender, intersex and queer psychology. Comprehensive in scope and international in outlook, it offers an integrated overview of key topical areas, from history and context, identities and fluidity, families and relationships, to health and wellbeing. The second edition has been extensively revised to address substantial developments and emerging areas, such as people born with intersex variations, transgender and non- binary genders, intersectionality, and gender diverse children. It also includes new pedagogical features to support learning and to facilitate discussion and reflection, with feature boxes throughout that explain important concepts, provide concise overviews of cutting-edge research, and offer first-person narratives that bring topics to life"--
Includes bibliographical references and index.
Keywords: Sexual minorities -- Psychology; Sexual minorities -- Psychology -- Problems, exercises, etc